Timing performance of the Timepix4 front-end. (1st July 2022) - Heijhoff, K.; Akiba, K.; Ballabriga, R.; van Beuzekom, M.; Campbell, M.; Colijn, A.P.; Fransen, M.; Geertsema, R.; Gromov, V.; Llopart Cudie, X.
Abstract: A characterisation of the Timepix4 pixel front-end with a strong focus on timing performance is presented. Externally generated test pulses were used to probe the per-pixel time-to-digital converter (TDC) and measure the time-bin sizes by precisely controlling the test-pulse arrival time in steps of 10 ps. The results indicate that the TDC can achieve a time resolution of 60 ps, provided that a calibration is performed to compensate for frequency variation in the voltage controlled oscillators of the pixel TDCs. The internal clock distribution system of Timepix4 was used to control the arrival time of internally generated analog test pulses in steps of about 20 ps. The analog test pulse mechanism injects a controlled amount of charge directly into the analog front-end (AFE) of the pixel, and was used to measure the time resolution as a function of signal charge, independently of the TDC. It was shown that for the default configuration, the AFE time resolution in the hole-collecting mode is limited to 105 ps. However, this can be improved up to about 60 ps by increasing the preamplifier bias-current at the cost of increased power dissipation. For the electron-collecting mode, an AFE time resolution of 47 ps was measured for a bare Timepix4 device at a signal charge of 21 ke. It was observed that additional input capacitance from a bonded sensor reduces this figure to 62 ps.